CHILD WITH COMBINED CARDIORESPIRATORY PATHOLOGY - N. D. Vashakmadze; G. V. Revunenkov; E. G. Chernavina; O. V. Kustova; M. V. Tarayan; I. V. Davydova; A. K. Gevorkyan (Union of pediatricians of Russia, 2013)
The course of a secondary pulmonary hypertension in a child with congenital heart disease and bronchopulmonary dysplasia in anamnesis is retraced in the article using a concrete clinical case. An assessment of echocardiographic and radiologic disease signs at a prolonged follow-up observation of a child with combined cardiorespiratory pathology was conducted. The main therapeutic approaches to this category of patients were covered.